Pengaruh Model Problem Based Learning terhadap Kemampuan Berpikir Kritis melalui Pemahaman Membaca pada Siswa Kelas XI SMA Negeri 7 Medan - Kusniawaty, Hetty; Trianton, Teguh; Purba, Christin Agustina (Universitas Nusantara PGRI Kediri, 2026)
The purpose of this study was to examine the effect of the problem-based learning model on students' critical thinking skills in reading comprehension, particularly in the 11th grade at SMA Negeri 7 Medan. This study employed a quantitative method with a quasi-experimental approach and a pretest-posttest design involving two groups: an experimental group and a control group. The study sample consisted of two classes with a total of 60 students. To collect data, the researchers used multiple-choice questions. The data were then analyzed through several stages, including pre-requisite statistical tests, including normality and homogeneity tests, and hypothesis testing using the t-test method. The results showed that the problem-based learning model did indeed impact students' critical thinking skills. This was evident from the posttest scores obtained, which were 85.73 in the experimental class and 66.30 in the control class. In the hypothesis testing, Ho was rejected and Ha was accepted because the t-value obtained (12.193) was greater than the t-table value (2.007). The conclusion of this study is that the use of the problem-based learning model has a positive impact on students' critical thinking skills in reading comprehension.